Analisis Bibiliometrik (2019-2023): Perkembangan Kondisi Janin Dalam Masa Prenatal - Apriani, Elsa; Nazwa Riyanti, Kayla; Rizqiyana, Nadya; Jubaedah, Siti; Widjayatri, RR. Deni (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Human development begins in the prenatal period, that is, a fetus that has matured during the prenatal period will grow and develop with normal weight, height and skin color. This condition greatly influences the low birth rate experienced by pregnant women if development is not optimal. The aim of this research is to determine the development of the fetus' condition during the prenatal period. The method used is bibliometric analysis, literature study and the Publish or Perish application with Google Scholar as a database for the years 2019-2023. After narrowing the results by selecting a special topic in